Association of initial national early warning score with clinical deterioration in pulmonary embolism - Anthony J. Weekes; Fernanda Calienescerpa; Kelly L. Goonan; Alexa L. Polzella; Melanie M. Hogg; Dalton Cox; Sean Flannigan; Emma Cruz; Halie A. O’Neill; Nathaniel S. O’Connell; Daniel R. Troha (Thrombosis Journal)
Abstract Background The National Early Warning Score (NEWS2) predicts clinical deterioration in hospitalized patients. Its role in pulmonary embolism (PE) risk stratification remains underexplored. This study assessed the association of initial NEWS2 with clinical deterioration and advanced interventions during hospitalization. Methods We retrospectively analyzed a PE response team (PERT) registry of adults with submassive and massive PE from 11 emergency departments (2016–2024). Initial NEWS2 was calculated for each registry patient. The primary outcome was in-hospital PE-related clinical deterioration (death, cardiac arrest, vasoactive medications for hypotension, or emergent respiratory interventions). The secondary outcome was advanced intervention use. We calculated odds ratios (OR) for different NEWS2 cut-offs. We used multivariable analysis to assess the association of NEWS2 and study outcomes, and decision curve analysis to determine net benefit of clinical deterioration. Results Among 2119 patients (mean age 62.2 [16.8], 51.2% female, 168 [7.9%] with massive PE, and 1951 [92.1%] with submassive PE), 309 patients (14.6%) experienced clinical deterioration and 488 (23.0%) required advanced interventions. Mean NEWS2 was higher in patients with vs. without clinical deterioration (6.0 ± 3.3 vs. 3.0 ± 2.4; p < 0.001) and in those with vs. without advanced interventions (4.8 ± 3.1 vs. 3.0 ± 2.5; p < 0.001). NEWS2 cut-off of ≥ 3 identified patients at risk of clinical deterioration: sensitivity 87% (82–90%), OR 6.1 (95% CI: 4.3–8.5), and negative predictive value (NPV) 96% (94–97%). NEWS2 cut-off ≥ 4 had specificity of 62% (60–65%), OR of 5.1 (95% CI: 3.9–6.7), and NPV of 94% (92–95%). As a continuous variable, NEWS2 had an OR of 1.2 (95% CI: 1.1–1.3). NEWS2 cut-offs from 3 to 5 showed an improved net benefit (0.08, 0.16, and 0.34) compared with treating all patients as high risk for clinical deterioration. Conclusion Patients with PE and initial NEWS2 scores ≥ 3 had a four-fold to eight-fold higher odds of clinical deterioration than those with NEWS2 < 3. NEWS2 is useful for predicting clinical deterioration and guiding intervention strategies in PE.